Dynamics Analysis for a Hierarchical System with Nonlinear Cut-off Interaction and Free Will (Analysis in Theory and Applications, 2024)
Noting that the particles communicate with each other within a finite distance, in the paper, we investigate the hierarchical model with free will and cut-offfunction (linear or nonlinear). As our observation, the cut-off size $r$ is a sensitive coefficient to achieve the flocking behavior. Besides we will use energy function to achievesome sufficient conditions to achieve a flock. The free-will represents the tendency ofthe particle itself to move. It will either facilitate or prevent cluster generation. Somenumerical simulations will validate our conclusions.